2021
DOI: 10.21608/jppp.2021.58388.1011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fortification of Mulberry Leaves with the Yeast Saccharomyces cerevisiae and the Blue Green Algae Spirulina platensis on some Quantitative Parameters of Silkworm Bombyx mori (L.)

Abstract: The present investigation was conducted to study the effect of fortification of mulberry leaves with different concentrations of baker's yeast Saccharomyces cerevisiae extract and blue-green algae Spirulina platensis extract on some quantitative parameters of Bombyx mori larvae and cocoons. Statistical analysis of the obtained data revealed that all larval treatments showed a significant increase in the larval and cocoon weights, especially at concentrations 0.5 % of yeast and 0.05% of spirulina. Feeding 5 th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The total haemolymph protein, haemolymph carbohydrates, haemolymph lipids were significantly increased due to the feeding the larvae with S. platensis mediated TiO 2 NPs at concentration of 50 ppm treated mulberry leaves (8.62 mg/ml and 8.63 mg/ml, 14.96 mg/ml and 14.97 mg/ml, 19.99 ml/g and 20.00 mg/g) as compared to control (7.68 mg/ml and 7.69 mg/ml, 13.97 mg/ml and 13.99 mg/ml, 19.05 ml/g and 19.06 mg/g) (Figure 1). This result corroborates with the findings of Soliman et al (2021) who observed that higher amount of total haemolymph protein at 0.05 percentage of Spirulina treated mulberry leaves. Similar, findings have been reported by Rani et al (2011) who recorded that supplementation of mulberry leaves with probiotics like S. cerevisiae and Spirulina increased the haemolymph protein and amino acids.…”
Section: Resultssupporting
confidence: 92%
“…The total haemolymph protein, haemolymph carbohydrates, haemolymph lipids were significantly increased due to the feeding the larvae with S. platensis mediated TiO 2 NPs at concentration of 50 ppm treated mulberry leaves (8.62 mg/ml and 8.63 mg/ml, 14.96 mg/ml and 14.97 mg/ml, 19.99 ml/g and 20.00 mg/g) as compared to control (7.68 mg/ml and 7.69 mg/ml, 13.97 mg/ml and 13.99 mg/ml, 19.05 ml/g and 19.06 mg/g) (Figure 1). This result corroborates with the findings of Soliman et al (2021) who observed that higher amount of total haemolymph protein at 0.05 percentage of Spirulina treated mulberry leaves. Similar, findings have been reported by Rani et al (2011) who recorded that supplementation of mulberry leaves with probiotics like S. cerevisiae and Spirulina increased the haemolymph protein and amino acids.…”
Section: Resultssupporting
confidence: 92%
“…A small cut was made with a knife on each cocoon at its one end and the pupa was removed to calculate the shell weight of each cocoon. The shell ratio of cocoon was calculated by the given formula: (Soliman, 2021) The protein (Sericin and Fibroin) contents were estimated by degumming method (Mumtaz et al, 2022). After degumming, the fibroin content was equal to dry weight of fibroin while given formula was used to evaluate sericin:…”
Section: Estimation Of Economical Traitsmentioning
confidence: 99%
“…These supplementations not only provide the necessary nourishment for improved growth and development but also improve economic characteristics [ 23 ]. Recently, amino acid fortified mulberry leaves has been introduced in Sericulture industry to improve the economic and biological traits of silkworm (larval growth, cocoon shell size and weight of silkworm) and the quality of silk produced [ [ [25] , [26] , [27] ]]. They can regulate and adjust the physiological function and metabolism of silkworms by joining active substances such as hormones and enzymes.…”
Section: Introductionmentioning
confidence: 99%